2018
DOI: 10.1021/acs.jmedchem.7b01468
|View full text |Cite
|
Sign up to set email alerts
|

Lipidated Brartemicin Analogues Are Potent Th1-Stimulating Vaccine Adjuvants

Abstract: Effective Th1-stimulating vaccine adjuvants typically activate antigen presenting cells (APCs) through pattern recognition receptors (PRRs). Macrophage inducible C-type lectin (Mincle) is a PRR expressed on APCs and has been identified as a target for Th1-stimulating adjuvants. Herein, we report on the synthesis and adjuvanticity of rationally designed brartemicin analogues containing long-chain lipids and demonstrate that they are potent Mincle agonists that activate APCs to produce inflammatory cytokines in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
96
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 48 publications
(100 citation statements)
references
References 51 publications
4
96
0
Order By: Relevance
“…This was first demonstrated in studies with linear TDEs, with longer lipids leading to a stronger pro-inflammatory response in vitro ( 48 , 60 ). A similar trend was observed with lipidated brartemicin derivatives, whereby it was also demonstrated that π-cation interactions were essential for the activity of the lead compound ( 62 ). The effect of lipid length on the immunomodulatory potential of Mincle agonists other than trehalose derivatives has also been demonstrated with, for example, longer chain GMCM and β-gentiobiosyl diacylglycerides derivatives showing enhanced Mincle activity compared to their shorter-chain counterparts ( 50 , 87 ).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…This was first demonstrated in studies with linear TDEs, with longer lipids leading to a stronger pro-inflammatory response in vitro ( 48 , 60 ). A similar trend was observed with lipidated brartemicin derivatives, whereby it was also demonstrated that π-cation interactions were essential for the activity of the lead compound ( 62 ). The effect of lipid length on the immunomodulatory potential of Mincle agonists other than trehalose derivatives has also been demonstrated with, for example, longer chain GMCM and β-gentiobiosyl diacylglycerides derivatives showing enhanced Mincle activity compared to their shorter-chain counterparts ( 50 , 87 ).…”
Section: Discussionsupporting
confidence: 73%
“…In another study, however, a glucosyl monomycolate derivate showed similar adjuvant activity to TDB in an in vivo OVA immunization model ( 27 ). Lipidated brartemicin derivatives have also shown enhanced in vivo adjuvant activity compared to TDB ( 62 ). In studies that identified the first endogenous ligand for Mincle, β-GlcCer, it was also demonstrated that ceramide, lactosyl ceramide and galactosyl ceramide were not Mincle agonists ( 91 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, our findings further illustrate species‐specific differences that may exist with regard to Mincle expression 17,46 . Lastly, as functional changes to Mincle agonists can further enhance the type 1 helper immune response, 17,47,48 this highlights the potential of developing additional Mincle agonists as anticancer adjuvants.…”
Section: Discussionsupporting
confidence: 53%